The relationship between National Intellectual Capital and corruption: a cross-national study - Stachowicz-Stanusch, Agata (Journal of Business Economics and Management, 2013)
The main objective of this paper is to examine the relationship between the National Intellectual Capital and the Corruption Perception Index. The analysis of the relationship between the NIC and the CPI was conducted for 16 countries: Austria, Belgium, the Czech Republic, Finland, France, Germany, Greece, Hungary, Ireland, Italy, Netherlands, Poland, Portugal, Spain, Sweden and the United Kingdom and was based on NIC data extracted from two sources (Carol Yeh-Yun Lin and Leif Edvinsson (2010), and the generational approach to the National Intellectual Capital measurement presented in the Report on the Intellectual Capital of Poland). Determination of the strength of the correlation between NIC and CPI represents the first step in evaluating intellectual capital as the factor which may reduce the scale of corruption. Evidence of a strong relationship between NIC and CPI confirms the author’s hypothesis that a strong relationship exists, at the same time proving that further studies must be carried out to determine the direction of this relationship. Based on the results of such research (providing that NIC is confirmed to have an effect on CPI), it will then be possible to recommend new methods of preventing corruption through the development of NIC. First published online: 12 Sep 2012